Cost Accounting: a managerial emphasis - Horngren; Datar; aFoster (Delhi : Pearson Prentic Hall, 2005)
Business
Keywords: Cost Accounting; Cost Accounting; Planning and Control; Cost information for Decisions; Cost Allocation and Revenues; Quality; Investment Decisions; Management Control Systems; Cost Terms and Purposes; Profit Analysis; Job Costing; Planning and Control; Management control; Inventory costing; Cost Behave; Pricing Decisions; Customer Profitability Analysis